Bacterial Uropathogens causing Urinary Tract Infection at Hetauda Hospital - Yadav, Ajay; Patel, Amit Kumar; Karna, Alina; Jha, Prashant (Nepal Journal of Health Sciences, 2023)
Introduction: Urinary tract infection is the infection of the uroepithelium that mainly affects kidney, ureter, urinary bladder and urethra. The causative agents of urinary tract infections are bacteria and fungi. Among these, bacteria are the most causative uropathogens of urinary tract infections.Objectives: The objective of this study is to isolate, identify, characterized and perform antibiotic sensitivity test from the bacterial isolates.Methods: A descriptive cross-sectional study was conducted from March 2023 to May 2023. Ethical approval was obtained from Institutional Review Committee (IRC), Madan Bhandari Academy of Health Sciences, IRC-32-079. Total of 1120 urine samples were collected during this study. Convenient sampling technique was used for this study. Clean catch or mid-stream urine was collected in a sterile container. All urine samples were submitted to Department of Microbiology for culture. A set of biochemical tests were done for bacterial identification. Antibiotic sensitivity test was performed by Kirby-Bauer disk diffusion method.Results: Total of 1120 urine samples were collected from patients suspected to Urinary Tract Infections. Total urine culture positive was 340 (30.36%). Of these bacterial isolates, Escherichia coli (248, 73%) was the most common species, followed by Klebsiella species (26, 7.6%), Staphylococcus saprophyticus (23, 6.76%) and Enterococcus fecalis (18, 5.3%).Conclusion: As prevalence of bacteria causing urinary tract infections is increasing day by day; so its proper isolation, identification, characterization with their antibiotic profile is necessary as it forms the base line for the clinicians to choose appropriate antimicrobial agents for empirical as well as rational treatment for UTIs.